Distinct local and systemic innate immune gene expression in response to Staphylococcus aureus-induced subclinical mastitis - Whelehan, Cormac (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Both local and systemic innate immune activity has a critical role in maintaining immunological homeostasis in the mammary gland. Dysregulation of the homeostatic process leads to increased infection and related pathology, either of which will affect quality and quantity of milk. Infections and inflammations of the mammary gland (mastitis) represent the most frequent and costly disease in dairy cows. Chronic, subclinical infections are of particular relevance. They impair the well-being of the host and cause ~80% of all mastitis related costs in dairy industries. Staphylococcus aureus is the bacteria most commonly isolated from cases of subclinical mastitis. However, limited information has been published to date on the innate immune response to S. aureus-induced subclinical mastitis.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.